2017
DOI: 10.1002/ardp.201700158
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Biological Evaluation of New Peptide Analogues as Selective COX‐2 Inhibitors

Abstract: A new class of peptide derivatives possessing SO Me and N pharmacophores at the para position of a phenyl ring bound to different aromatic amino acids were synthesized based on solid-phase synthesis methodology, and evaluated as selective cyclooxygenase-2 (COX-2) inhibitors. One of the analogues, i.e., compound 2a as the representative of this series, was recognized as the highest selective COX-2 inhibitor with a COX-2 selectivity index of >500. The structure-activity relationships (SARs) acquired indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Tyrosine and tryptophan are weakly hydrophobic amino acids; tyrosine does not serve a role in toxicity of ACPs, whereas tryptophan may exert a role in the toxicity of some ACPs against cancer cells such as indolicidin and trans-activator of transportation (TAT)-Ras GTPase-activating protein-326 peptides (19,58,59). However, synthesized peptides containing tryptophan and histidine may decrease cytotoxicity, while those containing tyrosine, phenylalanine or proline may be able to increase cytotoxic activity (60). The tryptophan position on the cell-penetrating peptides serves an important role in entering cancer cells, which subsequently involves an endocytic pathway and binding at the major groove of nuclear DNA (61).…”
Section: Anticancer Peptide: Physicochemical Property Functional Aspmentioning
confidence: 99%
“…Tyrosine and tryptophan are weakly hydrophobic amino acids; tyrosine does not serve a role in toxicity of ACPs, whereas tryptophan may exert a role in the toxicity of some ACPs against cancer cells such as indolicidin and trans-activator of transportation (TAT)-Ras GTPase-activating protein-326 peptides (19,58,59). However, synthesized peptides containing tryptophan and histidine may decrease cytotoxicity, while those containing tyrosine, phenylalanine or proline may be able to increase cytotoxic activity (60). The tryptophan position on the cell-penetrating peptides serves an important role in entering cancer cells, which subsequently involves an endocytic pathway and binding at the major groove of nuclear DNA (61).…”
Section: Anticancer Peptide: Physicochemical Property Functional Aspmentioning
confidence: 99%
“…Recently a new class of peptide derivatives was recognized as the highest selective COX-2 inhibitor with a COX-2 selectivity index of >500 (80). Ultimately, these drugs had a high risk of producing thrombotic cardiovascular events, and showed little improvement in preventing gastrointestinal ulcers (81).…”
Section: Conventional Cox-2 Inhibitorsmentioning
confidence: 99%
“…Negatively charged amino acids, such as aspartic acid and glutamic acid have antiproliferative activity on tumor cells [ 103 ]. Proline, tyrosine, and phenylalanine are characterized by their interaction with the phospholipids of the cancer cell membrane and increase the cytotoxicity of anticancer peptide [ 81 , 104 , 105 ]. It has also been observed that proline insertion tends to reduce helicity, similarly to D-amino acids, leading to reduced activity [ 63 ].…”
Section: Sequence Template Methods Of Rational Design Of Anticancementioning
confidence: 99%